2004
DOI: 10.1023/b:bebm.0000042711.31775.f7
|View full text |Cite
|
Sign up to set email alerts
|

Wound-Healing Effect of Papaya-Based Preparation in Experimental Thermal Trauma

Abstract: Treatment with the phytopreparation from papaya accelerated wound healing and reduced the severity of local inflammation in rats with burn wounds. The effect of this phytopreparation can be related to an increase in the effectiveness of intracellular bacterial killing by tissue phagocytes due to the inhibition of bacterial catalase. Antioxidant activity of the preparation decreases the risk of oxidative damage to tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 5 publications
0
34
0
2
Order By: Relevance
“…Its therapeutical value has been proven in several animal and human trials [13][14][15]. Papain and chymopapain are known to be effective in desloughing necrotic tissue, prevention of infection and the antimicrobial and antioxidant properties related to hydroxyl scavenging and iron chelating properties [15].…”
Section: Discussionmentioning
confidence: 99%
“…Its therapeutical value has been proven in several animal and human trials [13][14][15]. Papain and chymopapain are known to be effective in desloughing necrotic tissue, prevention of infection and the antimicrobial and antioxidant properties related to hydroxyl scavenging and iron chelating properties [15].…”
Section: Discussionmentioning
confidence: 99%
“…The use of various forms of papaya extract for the treatment of different skin diseases has also become widespread with in vitro and in vivo scientific validation (Hewitt et al, 2000, Mikhal'chik et al, 2004, Nayak et al, 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Mikhal'chik also showed that the wound healing was accelerated and the severity of local inflammation in rats with burn wounds was reduced (Mikhal'chik et al, 2004).…”
Section: Salmonella Typhi Staphylococcus Aureus Proteus Vulgaris Pmentioning
confidence: 94%
See 2 more Smart Citations